2002
DOI: 10.1095/biolreprod67.2.648
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor-I and Insulin-Like Growth Factor Binding Protein-2 and -5 in Equine Seminal Plasma: Association with Sperm Characteristics and Fertility1

Abstract: The objectives of this study were 1) to determine whether insulin-like growth factor-I (IGF-I) and insulin-like growth factor binding proteins (IGFBPs) were present in seminal plasma of stallions; 2) to compare semen parameters (IGF proteins, sperm numbers, morphology, and motility) from stallions at sexual rest (SR) and when sexually active (SA); 3) to compare semen parameters between stallions with high and low seminal plasma IGF-I concentrations; and 4) to examine the relationship between seminal plasma IGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
2
12

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 52 publications
3
35
2
12
Order By: Relevance
“…In the present study, no difference was observed between the genetic backgrounds (data not shown). In stallions, differences in IGF-I concentrations were not detected between samples from individual animals at different levels of sexual activity, but substantial variation in IGF-I concentrations occurred between stallions (Macpherson et al, 2002). In the present study, no correlation (p>0.05) was observed between the free IGF-I concentration in the seminal plasma of boars and most of the evaluated seminal parameters, except for the motility degradation rate.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…In the present study, no difference was observed between the genetic backgrounds (data not shown). In stallions, differences in IGF-I concentrations were not detected between samples from individual animals at different levels of sexual activity, but substantial variation in IGF-I concentrations occurred between stallions (Macpherson et al, 2002). In the present study, no correlation (p>0.05) was observed between the free IGF-I concentration in the seminal plasma of boars and most of the evaluated seminal parameters, except for the motility degradation rate.…”
Section: Discussioncontrasting
confidence: 75%
“…The knowledge of the number of receptors in different species may help to elucidate the true role of IGF-I in spermatozoal metabolism and the usefulness of this hormone in the improvement of artificial insemination programs. Pregnancy rates were higher for horses with high seminal plasma IGF-I levels (Macpherson et al, 2002), which is suggestive of the effects of IGF-I on sperm function.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, significant differences between both sexes were only found in foals aged 5-12 months and stallions aged 2-6 years. It is known that androgens increase the number of receptors for GH on the liver and therefore, greater release of IGF-1 to the bloodstream is expected (Clapper et al, 2000), even though it has been suggested that also the hepatic synthesis of IGF-1 is stimulated by both androgens and estrogens (McPherson et al, 2002). The period of time between two and four years of age is considered to constitute puberty in the Andalusian male and this fact could be one plausible explanation for the higher serum IGF-1 concentrations.…”
Section: Influence Of Sex On Serum Igf-1 Concentrations In Andalusianmentioning
confidence: 99%
“…It has also been shown that, immediately after the addition of this hormone in semen, sperm quality is improved in equine (Macpherson et al, 2002), buffalo (Selvaraju et al, 2009) and boar (Silva et al, 2011). Thus, a method to improve the quality of cooled boar semen could be the addition of a metabolic activator such as IGF-I, along with an antioxidant such as vitamin E.…”
Section: Introductionmentioning
confidence: 99%